PENGARUH EFIKASI DIRI DAN PENDIDIKAN KEWIRAUSAHAAN TERHADAP MOTIVASI MENJADI TECHNOPRENEUR MAHASISWA TEKNIK INFORMATIKA ANGKATAN 2016 UNIVERSITAS MULAWARMAN - FAHREZA HAMZI (Jurnal Administrasi Bisnis Fisipol Unmul, 2021)
This Research is quantitative research. Data collection techniques In this study used a questionnaire with the number of respondents 80 students of Informatics Engineering FKTI Unmul Samarinda class of 2016. Analysis tools used was multiple linear regression. Based on the results of research with multiple linear regression obtained means there is a low influence between self-efficacy and entrepreneurship education on motivation to become a technopreneur. With the results of the T test between self-efficacy on motivation to become technopreneur which means there is a significant influence. While the results of the T test between entrepreneurship education on motivation to be a technopreneur means there was no significant effect. From the results of research conducted, researchers give advice to the Informatics Engineering Study Program, namely: 1) Improve the facilities and infrastructure of the classroom information engineering laboratory and supply library space to support student activities. 2) Reactivate activities such as industrial visits or field trips to startup company and create bazaar to show student new discovery. 3) Implement OJT (On The Job Training) activities through cooperation in technology-based companies such as Telkom or Indonesian Bank for Informatics Engineering students to improve students ' entrepreneurial knowledge and skills. 4) empowering and building a partnership with alumni information engineering student program in implementation of technology based entrepreneurship program.